2019
DOI: 10.1364/optica.6.000244
|View full text |Cite
|
Sign up to set email alerts
|

Mapping and measuring large-scale photonic correlation with single-photon imaging

Abstract: Quantum correlation and its measurement are essential in exploring fundamental quantum physics problems and developing quantum enhanced technologies. Quantum correlation may be generated and manipulated in different spaces, which demands different measurement approaches corresponding to position, time, frequency and polarization of quantum particles. In addition, after early proof-of-principle demonstrations, it is of great demand to measure quantum correlation in a Hilbert space large enough for real quantum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…These quantum devices can be implemented in a large number of ways, for example, using ultracold trapped ions [6][7][8][9][10][11], cavity quantum electrodynamics (QED) [12][13][14][15], photonic circuits [16][17][18], silicon quantum dots [19][20][21], and theoretically even by braiding, as yet unobserved, exotic collective excitations called non-abelian anyons [22][23][24]. One of the most promising approaches is using superconducting circuits [25][26][27], where recent advances have resulted in devices consisting of up to 72 qubits, pushing us ever closer to realising so-called quantum supremacy [28].…”
Section: Introductionmentioning
confidence: 99%
“…These quantum devices can be implemented in a large number of ways, for example, using ultracold trapped ions [6][7][8][9][10][11], cavity quantum electrodynamics (QED) [12][13][14][15], photonic circuits [16][17][18], silicon quantum dots [19][20][21], and theoretically even by braiding, as yet unobserved, exotic collective excitations called non-abelian anyons [22][23][24]. One of the most promising approaches is using superconducting circuits [25][26][27], where recent advances have resulted in devices consisting of up to 72 qubits, pushing us ever closer to realising so-called quantum supremacy [28].…”
Section: Introductionmentioning
confidence: 99%
“…The main reason of this deviation from the theoretical prediction is that the second transforming zone after the interference section introduces differential losses for different channels, which further influences the out-coming results. This shortcoming can be overcome in the future by adopting the imaging-based large scale correlation measurement [27] since we could directly measure the 2D cross section structure.…”
Section: (A) a Femtosecond Pulse (140 Fs)mentioning
confidence: 99%
“…These results shows the capability of 3D structure and femtosecond laser writing technique. Such features combining on-chip photon generation [26] and imaging based large scale quantum correlation measurement [27] could open up a new regime for boson sampling.…”
mentioning
confidence: 99%
“…Single-photon-resolving cameras on the other hand naturally offer spatial or angular resolution, which can be exploited in super-resolved imaging [28][29][30][31][32], interferometry [33], characterization [34,35] or, similarly as in the previous case, observation of quantum interference effects such as in the Hong-Ou-Mandel-type experiments [36]. Recently however, the capability of cameras has been expanded by invoking a well-known mode conversion technique, in which Sun et al simply observed spectral correlation with the help of a diffraction grating [37]. It is thus a promising approach to use a camera to observe many DoFs simultaneously.…”
mentioning
confidence: 99%